Pengaruh Aplikasi Penyiraman Kalsium Klorida (Cacl2) Pratanam Dan Suhu Penyimpanan Pasca Panen Terhadap Daya Simpan Dan Kualitas Microgreen Wheatgrass (Triticum aestivum L.) Segar - Mardiyani, Siti Asmaniyah; Assyfa, Isna Khofifah; Muslikah, Siti (Universitas Islam Malang, 2023)
This study aimed to determine the effect of pre-planting application of calcium chloride (cacl2) and post-harvest storage temperature on the shelf-life and quality of fresh microgreen wheatgrass (Triticum aestivum l.). This study used a Randomized Block Design (RAK) with two factors. Factor 1 is CaCl2 concentration watering application, consisting of 5 levels, namely 0% concentration (C0), 1.5% concentration (C1), 3% concentration (C2), 4.5% concentration (C3), and 6% concentration (C4). Factor 2 is storage temperature, consisting of two levels, namely room temperature (S0) and low temperature (S1). The results of the observations concluded that there was an effect of storage temperature treatment on weight loss and chlorophyll content in microgreen wheatgrass. Wheatgrass stored at low temperature has a lower weight loss value than stored at room temperature. Wheatgrass stored at low temperatures has a higher chlorophyll content than stored at room temperature. Keywords: Microgreen, Wheatgrass, Calcium Chloride, Storage Temperature